Bimodal hybrid lightweight sound-absorbing material with high stiffness. (5th February 2019) - Ruan, Ju-Qi; Mosanenzadeh, Shahrzad Ghaffari; Li, Xin; Yu, Si-Yuan; Ma, Chu; Lin, Xin; Zhang, Shan-Tao; Lu, Ming-Hui; Fang, Nicholas X.; Chen, Yan-Feng
Abstract: An iron foam/silica aerogel composite (IFSA) with bimodal structure was designed and fabricated to solve the contradictions between acoustic damping and mechanical strength of a material. IFSA exhibits excellent broadband sound absorption performance with average absorption of ∼57% (500–6400 Hz) and maximum absorption coefficient of 0.995 at 4336 Hz, and high specific stiffness (1.6 × 10 5  m 2 s −2 ). The dissipation mechanism of sound energy in IFSA is well predicted by a designed bimodal model. Such fascinating artificial composite not only provides new insights for developing structural materials with high noise reduction and strength, but also has great potential applications for various fields.